Single-cell analysis of skeletal muscle macrophages reveals age- associated functional subpopulations - Krasniewski, Linda K; Chakraborty, Papiya; Chang-Yi, Cui; Mazan-Mamczarz, Krystyna; Dunn, Christopher; Piao, Yulan; Fan, Jinshui; Shi, Changyou; Wallace, Tonya; Nguyen, Cuong; Rathbun, Isabelle A; Munk, Rachel; et al. (bioRxiv, 2022)
Tissue-resident macrophages represent a group of highly responsive innate immune cells that acquire diverse functions by polarizing towards distinct subgroups. The subgroups of macrophages that reside in skeletal muscle (SKM) and their changes during aging are poorly characterized. By single-cell transcriptomic analysis, we found that mouse SKM macrophages primarily comprise two large populations, “healing” LYVE1+ and “proinflammatory” LYVE1-macrophages. SKM macrophages were further classified into four functional subgroups based on the expression levels of another cell-surface marker, MHCII: LYVE1+/MHCII-lo (similar to alternatively activated M2), LYVE1-/MHCII-hi (similar to classically activated M1), and two new subgroups, LYVE1+/MHCII-hi and LYVE1-/MHCII-lo. Notably, the new subgroup LYVE1+/MHCII-hi had traits of both M2 and M1 macrophages, while the other new subgroup, LYVE1-/MHCII-lo, expressed high levels of mRNAs encoding cytotoxicity proteins. Flow cytometric analysis validated the presence of the four macrophage subgroups in SKM. In old SKM, LYVE1- macrophages were more abundant than LYVE1+ macrophages. Furthermore, complementary unsupervised classification revealed the emergence of specific macrophage subclusters expressing abundant proinflammatory markers, including S100a8 and S100a9 in aged SKM. In sum, our study has identified dynamically polarized mouse SKM macrophages and further uncovered the contribution of specific macrophage subpopulations to the proinflammatory status in old SKM. Competing Interest Statement The authors have declared no competing interest.